Nurses' perceptions of patient safety culture: a mixed-methods study - Nina Granel; Josep Maria Manresa-Domínguez; Carolina Eva Watson; Rebeca Gómez-Ibáñez; Maria Dolors Bernabeu-Tamayo (BMC, 2020)
Abstract Background There are relatively few qualitative studies concerning patient safety culture. Methods We aimed to explore patient safety culture as perceived by the nursing staff in two public hospitals in Catalonia, Spain. A mixed-methods design was employed using a questionnaire, in-depth interviews, and non-participant observations. Results Sixty-two percent of the nursing staff rated patient safety as "Acceptable" but was not higher because of work pressure and lack of resources as perceived by staff. "Teamwork within units" had the highest rate of positive responses, and "Staffing" had the lowest rate. Emergency units showed more negative results than the other two units. Conclusions Safety incidents are not always reported due to fear of punishment, reflecting a lack of positive safety culture. It is necessary to design and implement strategies that promote a positive culture to avoid punitive responses and apply and evaluate these changes.